Solidarity in the Time of COVID-19: Refugee Experiences in Brazil - Martuscelli, Patricia (Refuge: Canada's Journal on Refugees, 2022)
Refugees have adopted solidarity actions during the COVID-19 pandemic, even after being left behind during health emergencies. This article contributes to the literature on solidarity and asylum by discussing refugees’ solidarity narratives towards vulnerable Brazilian groups, the refugee community, and the Brazilian population in general. The author conducted 29 in-depth semi-structured interviews with refugees living in Brazil between March 27 and April 6, 2020. Refugees’ past suffering experiences make them more empathic to other people’s suffering due to the pandemic, which creates an inclusive victim consciousness that seems to explain their solidarity narratives towards different groups.